Impacts of COVID-19 on agricultural production and food systems in late transforming Southeast Asia: The case of Myanmar - Boughton, Duncan; Goeb, Joseph; Lambrecht, Isabel B.; Headey, Derek D.; Takeshima, Hiroyuki; Mahrt, Kristi; Masias, Ian; Goudet, Sophie; Ragasa, Catherine; Maredia, Mywish K.; Minten, Bart; Diao, Xinshen (Elsevier, 2021)
The objective of this contribution is to report the initial impacts of measures taken to contain the COVID-19 pandemic on Myanmar's agri-food system. Myanmar is one of several late-transforming low-income countries in Southeast Asia where agriculture still plays a large role in rural livelihoods, and where food prices are a key factor affecting nutrition security for poor urban and rural households. Whereas the economic impacts of COVID-19 disruptions on tourism and manufacturing were obvious to policymakers, the impacts on the agri-food system were less evident and often more indirect. This resulted in the rural sector being allocated only a very small share of the government's initial fiscal response to mitigate the economic impacts of COVID-19. To correct this information gap, a suite of phone surveys covering a wide spectrum of actors in the agri-food system were deployed, including farm input suppliers, mechanization service providers, farmers, commodity traders, millers, food re